HUBUNGAN ANASTESI TERHADAP KESEHATAN REPRODUKSI PEKERJA KESEHATAN DI KAMAR OPERASI RS. RK. CHARITAS PALEMBANG - Yuniarti, Evi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Reproduction health is a biological process where a new individual is born. Wheres, anesthesia is a whole or partial loss of taste sesation caused by pathology in the neuron system of individual; anesthesia can also be defined as a technique in a medicine delivery (inhalation intravenous, or local) causing numbs partially or bodily for a certain period of time. This research aims at finding out wathers there is a correlation (correlations) between anesthesia and reproduction health disorders of health workers in operating room. This study belonges to analytic studi with cross sectional approach. This studi was done at roman catholic charitas hospital. The research samples were 52 health workers in a operating room at the hospital. The primary an secondary data were taken from questionnaires. Chi-Square (ɑ=0,05) and logistic regression werw used for data analysis technique. This research was done on June 22-30, 2015. At the end of the research, the univariate analysis results showed than there 63,5% of the respondens (Age>35), 88,5% (Highly Educated), 63,5% (Work Period ≥1 years), and 59,6% (Anasthesia Exposure) who did not suffer from the health reproduction disorders. Meanwhile, the bivariate analysis results indicated p values of the variables, i.e. Age (p value=0.021). work period (p value=1.000), education (p value=1.000, Work period (p value=0-020),  and anesthesia Exposure (p value = 0.003). the multivariate analysis results showed that age (p value=0.45) became the best predictor that can make the health workers suffer from reproduction disorders. It can be concluded that there were correlation between Age, work period and Anathesia Exposure with reproduction health Disorders. However, there was no correlation between Education and Health History with Reproduction Heath Disorders. As suggestions, the hospital should conduct any innovative program in order to avoid any secondary effect of the usage of anesthesia to the health works. Keywords : Reproduction Health disorders, Anesthesia Exposure